2016
DOI: 10.3168/jds.2016-11297
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: The use of an accelerometer for measuring step activity and lying behaviors in dairy calves

Abstract: Calf behaviors such as step activity, lying bouts, and lying time may be an indicator of calf health and welfare. To reduce time-consuming visual observations, the use of behavioral monitoring systems have been developed to capture these data. Previous studies have validated lying behaviors using an accelerometer (HPG; HOBO Pendant G data logger, Onset Computer Corp., Bourne, MA) in calves. However, the HPG does not measure step activity. The objectives of this study were to (1) validate step activity, lying b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 16 publications
6
25
2
2
Order By: Relevance
“…Cohen's kappa was calculated as 0.88, which indicates an almost perfect agreement. These results are similar to those reported by Bonk et al (2013) and Swartz et al (2016), who found high correlations between data logger and direct or video observation for lying behavior in calves. Discrimination between standing and locomotion was not yet feasible because the intervals during which calves were engaged in locomotion were too short (i.e., the mean duration of single locomotion episodes was 4 s, and episodes rarely lasted longer than 10 s) to be detected by the algorithm.…”
supporting
confidence: 91%
“…Cohen's kappa was calculated as 0.88, which indicates an almost perfect agreement. These results are similar to those reported by Bonk et al (2013) and Swartz et al (2016), who found high correlations between data logger and direct or video observation for lying behavior in calves. Discrimination between standing and locomotion was not yet feasible because the intervals during which calves were engaged in locomotion were too short (i.e., the mean duration of single locomotion episodes was 4 s, and episodes rarely lasted longer than 10 s) to be detected by the algorithm.…”
supporting
confidence: 91%
“…Daily lying time of each cow, suggested by Drissler et al (2005) as an indicator of animal welfare, was recorded daily by an automatic meter located within each cow's pedometer tag (Afimilk Ltd.). This lying tag was validated by Swartz et al (2016).…”
Section: Milk Performance Bw Measurements Activity and Lying Timementioning
confidence: 99%
“…In addition, there is a need to identify automated methods of characterizing dairy calves, especially for exploration-activity and fearfulness, as currently it is likely not feasible to collect these measures on-farm. Automated activity monitors (Swartz et al, 2016), or the response to an approaching human during feeding (Lensink et al, 2003;Rousing et al, 2005), are examples of practical assessment methods that should be verified for associations with weaning age, feeding behavior, and performance.…”
Section: Fearful and Exploratory-active Personality Traitsmentioning
confidence: 99%